JURIDICAL ANALYSIS OF THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 91/PUU-XVIII/2020 ON LAW NUMBER 11 YEAR 2020 - Syofyan, Yunita; Nazmi, Didi (UNES Law Review, 2023)
The interest of the people is the formation of rules that are able to accommodate the eye of the law. Article 20 paragraph (1) of the 1945 Constitution states that "The House of Representatives holds the power to make laws. The formation of a regulation carried out by the parliament is a manifestation as a state of law, the state is obliged to carry out the development of national law which is carried out in a planned, integrated and sustainable manner in the national legal system that guarantees the protection of the rights and obligations of all Indonesian people based on the Constitution of the Republic of Indonesia in 1945. This research is a normative law (doctrinal research), namely. In normative legal research, research is carried out through library research. The results of this study indicate that the Implications of the Constitutional Court Decision Number 91 of 2020 have the consequence of a formation of legislation without reflecting the principle of legal certainty and the principle of openness must be declared procedurally flawed in order to protect the public from the interests of legal product makers. The follow-up to the Constitutional Court Decision Number 91 of 2020 that tolerance for a legally defective product must not be re-applied even though the constitutional judge provides conditions as long as it is repaired for 2 (two) years, especially the Job Creation law. Thus, legal products must have concrete legal force in order to obtain legal certainty.